2021
DOI: 10.1097/txd.0000000000001128
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Lung Allograft Dysfunction Associated With Aspergillus Infection

Abstract: Background. We sought to determine whether invasive aspergillosis (IA) during the first year after lung transplantation increased the risk of chronic lung allograft dysfunction (CLAD). Methods. We retrospectively reviewed the records of 191 patients who underwent lung transplantation at our institution between January 2013 and December 2017. Screening for Aspergillus was with bronchial aspirates, bronchoalveolar lavage if indicated or during surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 34 publications
2
8
0
Order By: Relevance
“…This retrospective study of prospectively collected data in a large cohort of LTx recipients demonstrated for the first time that Aspergillus species specific IgG was associated with later fungal isolation and fungal-related complications (IFD,CLAD). This study also confirmed previously published findings that mold isolation, especially Aspergillus species, was associated with CLAD development and impaired survival ( 3 5 ).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…This retrospective study of prospectively collected data in a large cohort of LTx recipients demonstrated for the first time that Aspergillus species specific IgG was associated with later fungal isolation and fungal-related complications (IFD,CLAD). This study also confirmed previously published findings that mold isolation, especially Aspergillus species, was associated with CLAD development and impaired survival ( 3 5 ).…”
Section: Discussionsupporting
confidence: 92%
“…Invasive fungal infections are a known risk factor for CLAD, and even without signs of infection Aspergillus species isolation from airway sampling is considered a risk factor for CLAD. In our study, Aspergillus species were cultured in 74.3% of the respiratory samples demonstrating molds, and Aspergillus species isolation was significantly associated with CLAD and impaired survival, confirming findings from earlier studies ( 2 5 ). There was no significant difference in CLAD occurrence in patients with Aspergillus IFD vs. non-IFD Aspergillus isolation.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations